Chloride Ingress in Chemically Activated Calcined Clay-Based Cement. (2nd May 2018) - Marangu, Joseph Mwiti; Thiong'o, Joseph Karanja; Wachira, Jackson Muthengia
Abstract : Chloride-laden environments pose serious durability concerns in cement based materials. This paper presents the findings of chloride ingress in chemically activated calcined Clay-Ordinary Portland Cement blended mortars. Results are also presented for compressive strength development and porosity tests. Sampled clays were incinerated at a temperature of 800°C for 4 hours. The resultant calcined clay was blended with Ordinary Portland Cement (OPC) at replacement level of 35% by mass of OPC to make test cement labeled PCC35. Mortar prisms measuring 40 mm × 40 mm × 160 mm were cast using PCC35 with 0.5 M Na2 SO4 solution as a chemical activator instead of water. Compressive strength was determined at 28th day of curing. As a control, OPC, Portland Pozzolana Cement (PPC), and PCC35 were similarly investigated without use of activator. After the 28th day of curing, mortar specimens were subjected to accelerated chloride ingress, porosity, compressive strength tests, and chloride profiling. Subsequently, apparent diffusion coefficients (D a p p ) were estimated from solutions to Fick's second law of diffusion. Compressive strength increased after exposure to the chloride rich media in all cement categories. Chemically activated PCC35 exhibited higher compressive strength compared to nonactivated PCC35. However, chemically activated PCC35 had the least gain in compressive strength, lower porosity, and lower chloride ingress in terms ofD a p p, compared to OPC, PPC, and nonactivated PCC35.